INFLUENCE OF TIKTOK ADVERTISEMENT ON BRAND IMAGE AMONG PRIVATE UNIVERSITY STUDENTS IN NIGERIA - O. Osueke, Ngozi; Oyekola, Isaac; Olatunde, Abdullahi; C. Ibenyenwa, Ndidi; S. Ogundoyin, Olayinka (African Journal of Social and Behavioural Sciences, 2024)
Considering the increasing use of TikTok among young generations, this study examines the role of TikTok influencers in shaping the image of advertised brands, the influence of TikTok advertisements on brand image, and best practices for optimizing TikTok advertising strategies. A descriptive cross-sectional research design was employed to collect quantitative data from 367 students at a private university in Nigeria via a purposive cluster sampling technique, and the data were analysed via descriptive analyses at the univariate, bivariate and multivariate levels. The results show that social media influencers play major roles such as creativity and innovation, humour and entertainment, use of popular influencers, appeal to followers‟ emotions, visual aesthetics, and clear messaging to shape the perceptions of advertised brands. Additionally, there is a statistically significant association between the frequency of TikTok usage and the enhancement of brand image [φc = 0.21, χ2(8) = 66.38, p<0.001] and between the awareness of brand advertisements on TikTok and the enhancement of brand image [φc = 0.21, χ2(2) = 15.36, p<0.01]. In addition, the frequency of TikTok usage significantly predicts brand image enhancement, t(364) = 22.29, p < .001. Finally, user-generated content on TikTok, product demonstrations, influencer collaboration, and behind-the-scene videos are the most effective content for enhancing brand image. The study concludes that TikTok advertisements influence brand image and that social media influencers play key roles in shaping the perceptions of advertised brands. It is recommended that brand companies advertise their brands through TikTok to enhance their brand image and for maximum impact.